PENDIDIKAN KARAKTER BERBASIS KELUARGA - Jalaluddin Jalaluddin (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2012)
The Indonesian nation is currently experiencing a degradation of almost all lines of social and moral life. The rise of cases of domestic violence, human trafficking, juvenile delinquency,